An Index Measuring State Capacity, 1789–2018. (17th February 2022) - O'Reilly, Colin; Murphy, Ryan H.
Abstract : This paper contributes to the literature on state capacity by developing a method that yields an index of state capacity with far more comprehensive data coverage across time and countries than has been possible previously. Unlike narrower measures of fiscal capacity or legal capacity, the index is more comprehensive, using data from the Varieties of Democracy dataset on fiscal capacity, a state's control over its territory, the rule of law, and the provision of public goods used to support markets. Like the previous literature, it demonstrates that the historical prevalence of warfare predicts state capacity. Several exercises are performed to demonstrate the validity of the index in measuring state capacity.